Investigation of Stability of Olive Oils Aromatized with Some Local Plants - Buket Aydeniz-Guneser (Turkish Journal of Agriculture: Food Science and Technology)
The aims of this study were to evaluate the total phenolic and pigment contents of five edible plants collected from Eastern Black Sea region and to test the storage stability of extra virgin olive oils aromatized with traditionally consumed plants. Aromatized extra virgin olive oils were prepared by addition of dry forms of local plants such as mendek (Aegopodium podagraria L.), çalıçilek (Vaccinium myrtillus L.), galdirik (Trachystemon orientalis L.), sakarca (Ornithogalum umbellatum L.) and hırnık (Diospyros lotus L.). Changes in the quality status of extra virgin olive oil were monitored with free fatty acid, peroxide value, total phenol content, pheophtyin a, lutein and beta carotene analyses during 5-month storage period at 24°C. Furthermore, hue and chrome values, total phenolic, chlorophyll and carotene contents were also analysed to determine the characteristic properties of plant samples. The addition of mendek and çalıçilek have remarkable effects on the transfer of phenolic compounds and pigments from plants to oil during all storage. It was determined that the addition of plant materials can improve the oil stability and cause to a lower free fatty acid and peroxide values in aromatized extra virgin olive oils. Obtained findings suggest that the aromatized olive oils with local plants is sensorial and nutritionally acceptable and can be used safely in aromatization and preparation of healthy and tasty foods at non-thermal process.